2013
DOI: 10.1080/09602011.2012.726925
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cognitive fatigue in MS patients through cognitive and physical load

Abstract: The objective of the study was to investigate whether cognitive fatigue in patients with multiple sclerosis (MS) is a spontaneous phenomenon or whether it can be provoked or exacerbated through cognitive effort and motor exercise. Thirty two patients with definite MS and cognitive fatigue according to the Fatigue Scale for Motor and Cognitive Functions (FSMC ≥ 22) performed attention tests (alertness, selective, and divided attention subtests from the TAP test battery for attention performance) twice during re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 26 publications
1
37
0
4
Order By: Relevance
“…One limitation in our study is that we did not screen our subjects for chronic fatigue syndrome, a common comorbidity with FM. In people with multiple sclerosis, traumatic brain injury, cancer, and cognitive fatigue syndrome, both cognitive fatiguing tasks and physical fatiguing tasks increase perceived cognitive fatigue ().…”
Section: Discussionmentioning
confidence: 99%
“…One limitation in our study is that we did not screen our subjects for chronic fatigue syndrome, a common comorbidity with FM. In people with multiple sclerosis, traumatic brain injury, cancer, and cognitive fatigue syndrome, both cognitive fatiguing tasks and physical fatiguing tasks increase perceived cognitive fatigue ().…”
Section: Discussionmentioning
confidence: 99%
“…Patients completed the Fatigue Scale of Motor and Cognition (FSMC) 15 questionnaire, as well as the Becks Depression Inventory (BDI) 16 on the day of the experiment. Participants performed in the alertness task from the Test-battery of Attentional Performance (TAP), 17 a simple visual reaction task shown to be sensitive to cognitive fatigue [18][19][20] before and after the MRI measurement. vision (FOV) = 192 mm, flip angle = 80°, TR = 2.5 seconds, TE = 30 ms while participants performed in the N-back task.…”
Section: Behavioral Measurementsmentioning
confidence: 99%
“…In the meantime, other groups have independently shown an association between alertness and the subjective feeling of fatigue: Weinges-Evers et al[3] reported higher reaction times in alertness in patients with higher levels of fatigue (Fatigue Severity Scale ≥4.0) compared to those without fatigue in a large study with 110 MS patients, whereas other neuropsychological tests could not differentiate between both groups [3]. Accordingly, measurement of alertness has been proposed as the most sensitive test for evaluating fatigue [21], and mean reaction times in the subtest “Alertness” were significantly higher in MS patients with fatigue compared to healthy controls, with an increase during cognitive load, which was in contrast to the results in controls who showed a decrease in reaction times after cognitive demanding tasks [4]. …”
Section: Discussionmentioning
confidence: 99%